Thermal examination for double diffusive MHD Jeffrey fluid flow through the space of disc and cone apparatus subject to impact of multiple rotations - Khan, Arshad; Gul, Taza; Ali, Ishtiaq; Abd El-Wahed Khalifa, Hamiden; Muhammad, Taseer; Alghamdi, Wajdi; Shaaban, Abeer A. (The International journal of heat and fluid flow, 2024)
•The current work aims to study the double diffusive MHD Jeffrey fluid flow through the space of disc and cone apparatus subject to impact of multiple rotations.•Growth in magnetic, Jeffery fluid, and Maxwell factors retards the radial velocity.•Augmentation in the thermophoresis factor results in in an expansion in concentration and thermal distributions.•Growth in the Brownian motion factor supports thermal panels and opposes concentration panels.•Thermal distribution retards with growth in thermal relaxation factor and Prandtl number.•It has also been revealed from this work that growth in Nb,Nt,M,λ, and λ1 the thermal transference, rate has experienced a respective variation of 30%, 35%, 20%, 8%, and 7% showing the highest growth in case of variations in the thermophoresis factor. Non-Fourier’s and non-Fick’s models enhance predictions of transient heat transfer and mass transport, especially in situations where local equilibrium assumptions break down. In such fluids, the deformation rate and shear stress display a natural parabolic structure. In this study, we explore the flow of a Jeffrey fluid with dual diffusions, incorporating both non-Fourier's and non-Fick's assumptions, through the gap of disk-cone devices. Four scenarios have been investigated for fluid flow and heat transformation in this work comprising of (i) both disc and cone are rotating in opposite directions (ii) both disc and cone are rotating in same direction, (iii) cone is rotating while disc remains stationary, (iv) disc is rotating while cone remains stationary. After deriving the basic equations, a set of appropriate variables is used to convert them into dimension from form. RK-4 (Runge-Kutta 4th order) technique has been employed for the solution of nonlinear equations. As the magnetic and Maxwell factors experience a notable increase, whether the disk and cone move in tandem, in opposite directions, or involve a static cone with a gyrating disk, or a static disk with a gyrating cone, the transverse velocity panels consistently exhibit retardation in all scenarios. Additionally, a noteworthy observation is made when evaluating changes in both the Nusselt number and the Sherwood number, with significantly more pronounced variations detected at the surface of the disk compared to that of the cone. There has been a 35% increase observed in the thermal flow rate with variations in the thermophoresis factor.